PYOMETRA EVALUATION STUDY 15 YEARS IN THE HOSPITAL LOAYZA - Sandoval Jiménez, Roberto (2015)
Nine cases of pyometra occurred is reviewed retrospectively for a period of 15 years in the Archbishop Loayza Hospital Lima-Peru. The diagnosis was established clinically after observation of purulent material escaping through the cervical opening spontaneously or after dilation of the cervix. The average age was 52.5 years. Seven patients were post-menopausal age. The symptoms of malodorous vaginal discharge purulent discharge occurred in seven patients, five of whom attended with fever and general commitment. In no event associated with malignant disease of the cervix or uterus it is found. In six cases enlarged uterus was found and, in all cases, this was painful on palpation. EI preoperative diagnosis was made in four cases. Bacteriological results are limited by not having done anaerobic cultures. All patients received medical and surgical treatment, and its evolution was favorable. The results based on an updated literature review discussed.